L'economie du Nigeria. Agriculture et elevage - International Livestock Centre for Africa (1979)
Study on the contribution of agriculture and the livestock sector to the Nigeria national economy, w. data on trend of agricultural production, import, export and prices of agricultural products, geographic distribution of livestock, meat supplies and livestock development projects in third national plan.